The relationship between emotional intelligence and academic achievement : a correlational study of undergraduate students at the University College of Education Zanzibar - Issa, Nyezuma Simai (Institute of Education, International Islamic University Malaysia, 2012)
The main purpose of the study was to examine the relationship between emotional intelligence and academic achievement of undergraduate students of the University College of Education 2.anzibar (UCEZ). The ability-based model of emotional intelligence was utilized through the emotional intelligence inventory developed by Martha Tapia and Judith Burry-Stock (1998) to obtain data from 215 students who were randomly selected from arts and science specializations and their CGP A .was used to measure academic achievement. Out of the 215 questionnaires distributed, 210 questionnaires were returned for the statistical analysis and the data was analyzed using the Pearson correlation coefficient, t-test statistic and ANOV A. The results revealed that there is no significant relationship between emotional intelligence and academic achievement. Although the study showed significant statistical difference in the academic majors of UCEZ students, no significant difference was found between demographic characteristics and emotional intelligence.